Community Engagement Research: Harnessing Natural Materials for Ecoprint Totebags - Arina Himatul Husna; Desy Mairita; Fakhrurrozi Fakhrurrozi; Tiy Kusmarrabbi Karo; Jeri Fernando; Iwan Napitupulu; Mutiara Syakila; Gusna Citra (ASSUNNAH PRESS, 2023)
The aim of this research-based community service is to provide creative space for youth and children in the Simpang Tiga village by applying the Community-Based Participatory Research approach. (CBPR). The activity focuses on the development of skills in the manufacture of canvas totebags using ecoprint techniques based on natural pigments from leaves around resident settlements. The dedication team delivered the material through a lecture approach as well as a question-and-answer session followed by a demonstration and practical production of the ecoprint totebag. The responses from the participants indicated a high level of enthusiasm, with the majority revealing that these activities add value to the use of their time. The expectation of the participants is that there will be continued activities on a periodic basis to produce products that are more diverse and beneficial to the community.